Three-dimensional trajectories of cultivated Pacific bluefin tuna Thunnus orientalis in an aquaculture net cage - K Komeyama (Inter-Research, 2013)
Swimming trajectories of aquatic animals that are estimated using the dead-reckoning technique below the sea surface tend to have very large associated observational errors. Therefore, the aim of the present study was to develop a technique for removing accumulated errors from such trajectories for Pacific bluefin tuna Thunnus orientalis. Horizontal and vertical speeds and heading angle were measured in an aquaculture net cage using 2 types of data loggers, and current velocity was recorded at a depth of 12 m to measure the tidal current speed around the net cage. Fourier analysis indicated that the primary source of error in trajectory estimates was the effect of ocean currents, which resulted in drift, and further analysis revealed that the frequency contributing to drift was consistent with the low-frequency signal in a spectrum analysis of horizontal speed. Therefore, a high-pass filter was applied to horizontal speed data to remove any frequencies lower than the cut-off frequency (0.0015 Hz), following which these data were back-transformed into a time domain that no longer included the drift effect caused by the current. The reconstructed trajectories fit within the inner diameters of the net cage, indicating that they were realistic. To confirm the validity of the resultant swimming trajectories, a flume tank experiment was conducted, which demonstrated that the high-pass filter effectively removed current drift from the estimated trajectory. Furthermore, since the method was estimated to have a precision of approximately 0.20 m, it not only allows the 3-dimensional trajectories of circling tuna to be estimated but can also be applied to the behavior of fish in the wild.